2002
DOI: 10.1021/ja028656a
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite-Coated Mesostructured Cellular Silica Foams

Abstract: ZSM-5- and NaY-coated MCF materials as new acid catalysts for conversion of bulky molecules were prepared by the coating procedure using diluted clear zeolite gel solutions. The resulting materials have high acidity and improved steam stability as compared to that of the corresponding MCF aluminosilica. This could be due to the zeolitic nature and relative hydrophobicity of the mesopore surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(72 citation statements)
references
References 21 publications
1
71
0
Order By: Relevance
“…microcrystalline-structure zeolites [33][34][35] (Beta, ZSM-5, Y, and others) by means of ah ydrothermalc rystallization approach to synthesize pure mesoporous silica are the main solutions. Bao and co-workers [31] prepared ano rdered mesoporous Al-SBA-15 support by an ew synthesis approach, and the NiW supported catalystw as used for DBT HDS evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…microcrystalline-structure zeolites [33][34][35] (Beta, ZSM-5, Y, and others) by means of ah ydrothermalc rystallization approach to synthesize pure mesoporous silica are the main solutions. Bao and co-workers [31] prepared ano rdered mesoporous Al-SBA-15 support by an ew synthesis approach, and the NiW supported catalystw as used for DBT HDS evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their properties which combine the benefits of both zeolites and mesoporous materials, namely the high acidity and mesoporosity, they might be envisioned as efficient catalysts in applications involving bulky hydrocarbons. Though successful approaches to synthesize such materials have been reported [3][4][5][6][7][8][9][10][11][12][13][14], their acidity and catalytic activity still remain an issue under debate. Up to the present time, the test reactions used to characterize these new materials are mainly the cracking of cumene [3,6,7,10] or 1,3,5-triisopropylbenzene [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In 1992, it has been reported that mesoporous materials with highly ordered pore structures have potential applications in catalysis, adsorption and separation of molecules because of their high surface areas, large pore volume, and tunable uniform pore structures, but they show relatively weak acid strength [22][23][24][25][26][27][28]. To increase the acid strength of mesoporous materials, sulfated zirconia was introduced into the mesopores such as MCM-41 [29][30][31][32][33][34], FSM-16 [35], and SBA-15 [36,37].…”
Section: Introductionmentioning
confidence: 99%